Blood donation in a large urban centre of southeast Brazil: a population‐based study. Issue 1 (29th February 2016) - Moreno, E. C.; Bolina‐Santos, E.; Mendes‐Oliveira, F.; Miranda, C.; Sabino, E. C.; Cioffi, J. G. M.; Camargos, V.; Caiaffa, W.; Xavier, C. C.; Proietti, F. A.; de Freitas Carneiro‐Proietti1, A. B.
SUMMARY: Objectives: This study aimed to estimate the prevalence and characterise potential blood donors and non‐donors in a well‐populated and representative urban area of Southeastern Brazil. Background: Studies on blood donation usually evaluate individuals who donate. Population‐based studies may contribute to characterise those who never reach the blood centre, trying to increase the range of donors. Study Design and Methods: This was a secondary analysis of a population‐based survey and a blood donor motivation study [Recipient Epidemiology and Donor Evaluation study (REDS II) International]. In a cross‐sectional study 4047 individuals representing a metropolitan area answered the question 'Have you ever donated blood at least once in your life?'. The profiles ('Yes/No') were compared. Non‐donors from this reference population were compared with donors of a local blood center, in a case control analysis. Results: A total of 69·0% of the population had never donated blood and was composed mostly of women, younger than 30 years old, people not contributing to social security and not subscribing to newspapers. In the case–control study, the likelihood of donating was higher for: men, younger than 50 years old, longer time of education, married, participating in political campaigns and with a good self‐perception of health. The factors associated with no blood donation were: self‐reported mixed or white race/ethnicity, income higher than two minimum wages and belonging to trade union, political, religious/spiritual, or other social group and worse self perception of health. Conclusions: This population‐based study allowed us to characterise a high proportion of people that never reaches the blood centre. The results may be used to diversify the donor profile, creating strategies to target those least likely to donate blood, as women, white people and those with higher income and purchasing power.